AGRIBUSINESS AS THE SOLUTION FOR THE UNDERUTILIZED WAQF LANDS: A VIEWPOINT FROM THE WAQF ADMINISTRATORS - Ali Azizan, Norfaridah; Muhamat, Amirul Afif; Syed Alwi, Sharifah Faigah; Ali, Husniyati; Jaafar, Mohamad Nizam; Jusoh, Nur Hidayah (PLANNING MALAYSIA, 2021)
Waqf land bank in Malaysia has huge potential to be developed but most of the lands are underutilized due to the administrative and legal (conventional and Shariah) issues that are plaguing them. The underutilized land size is estimated to be around 87% from the 30,000 hectares waqf lands, as at 2018. This study focuses on Selangor and Perak to explore on the same issue by interviewing the relevant key informants to gather their feedback. In order to unlock the potential of these waqf lands, pragmatic model or approach needs to be researched and implemented - and this study suggests agribusiness. Therefore, this study embarks on the preliminary field work that intends to assess the potential to develop the waqf lands in Selangor and Perak for agribusiness activities.